Analisis Strategi Dakwah dalam Perspektif Komunikasi Persuasif pada Konten Media Sosial sebagai Media Pendidikan Agama Islam di Era Digital : Analysis of Da'wah Strategy from the Perspective of Persuasive Communication in Social Media Content as a Medium of Islamic Religious Education in the Digital Era - Muhammad Albi; Anita Puji Astutik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The development of digital media has transformed da'wah patterns from conventional approaches into more interactive practices that reach wider audiences through social media platforms. This phenomenon raises the need to systematically examine how da'wah strategies are designed and implemented within the framework of persuasive communication, particularly in the digital da'wah content developed by Ustadz Adi Hidayat. This study aims to examine the pattern of da'wah strategy, analyze the implementation of persuasive communication principles (ethos, logos, and pathos), and assess the effectiveness of the strategy in influencing audience understanding and attitudes. This study employs a descriptive qualitative method with a content analysis approach toward da'wah material documented in video and transcript form, supported by secondary data from relevant academic literature. The findings show that Ustadz Adi Hidayat's da'wah strategy simultaneously integrates the three rhetorical elements: ethos built from academic and scholarly credibility, logos constructed through systematic explanation and whiteboard visualization, and pathos delivered through the bil mau'izhah al-hasanah approach. These three elements are proven effective in encouraging voluntary changes in religious understanding and attitudes among the audience. This study contributes theoretically and practically to the development of systematic digital da'wah strategies grounded in persuasive communication principles in the digital era.